Ecological Inequality of Village-City : Study of the Operational Impact of Terjun Medan Landfill on Environmental Quality and Public Health of Surrounding Villages - Novida Yenny; Mulhady Putra; Nurida Hana Simamora; Pinta Yosepin Turnip (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Garbage become problem complex in life urban areas , especially in Medan as Mother city North Sumatra Province . Research This analyze impact management Trash in Place Disposal End (TPA) Terjun , Medan Marelan District , regarding environment surrounding area . Method study use approach qualitative with technique observation , interviews , and studies documentation . Research results show that TPA Terjun has​ area 14 hectares Not yet managed optimally , with the dominant open dumping system . The impacts that arise covering groundwater pollution , pollution​ air , disturbance aesthetics , as well as improvement vector disease . Findings This reinforced by BPS data (2018) which shows density Medan 's population reached 8,342 people /km², correlated with high volume of waste . Research This recommend implementation system management rubbish integrated based on principle health environment and economy circular For reduce impact negative .